The Alteration in Parathyroid Hormone and Calcitonin of Pregnant Women in Babylon Governorate - Hammadi, Hossam; Alta'ee, Abdulsamie; Musa, Ban (Journal of Biomedicine and Biochemistry, 2023)
Background The peptide hormones parathyroid hormone (PTH) and calcitonin (CT) both work on osteoblasts (bone-forming cells) and osteo- clasts (bone-resorbing cells) to regulate calcium homeostasis.Aims of the study This study aimed to evaluate the changes in serum levels of parathyroid hormone and calcitonin in pregnant and non-pregnant women in Babylon Governorate, Iraq.Materials and methods This study designs as a case-control study performed on pregnant women who attended Women’s and Children’s Hos- pital in Hilla and Shomali General Hospital in Babylon Governorate. Forty pregnant women with a range age (18-40 years) and 50 healthy subjects with non-pregnant women with range age (18-40 years) visited the hos- pital for routine check-ups without any history of chronic diseases, acute illness and infection. The biochemical parameters were determined by the sandwich ELISA technique.Results The results show a significant increase in levels of parathyroid hormone (PTH) and calcitonin (CAL) in pregnant as compared with the non-pregnant group (277.7 ± 47.87 ng/mL),( 72.58 ± 12.76 ng/mL) and (21.89 ± 4.412 ng/mL), ( 9.65 ± 1.921 ng/mL) respectively. The significant difference (p-value < 0.0001).Conclusion In conclusion, the present study finds that pregnant women experience significant hormonal changes in PTH and CT, which indicates the necessity of diagnosing these changes and treating them for the success of this pregnancy.